A kind of carbon-coated foil material and its preparation method and application
By using a layered porous carbon material coating with gradient porosity and an ordered porous carbon material with two-dimensional hexagonal morphology on the lithium-ion battery electrode, the problem of limited diffusion of lithium ions within the porous electrode is solved, and the battery's magnification is significantly improved Performance and electrode conductivity extend the service life of the battery.
Patent Information
- Application Number
- CN202211412135.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-11-11
AI Technical Summary
During the charging and discharging process of existing lithium-ion batteries, the diffusion of lithium ions inside the porous electrode is limited, resulting in poor rate performance, and carbon-coated current collectors cannot effectively improve the overall performance of the battery, especially rate performance.
Use a porous carbon material coating with different porosities, the porosity away from the foil side is greater than that near the foil side, and a gradient porosity structure is formed through the etching liquid and sintering process, combining the two-dimensional six-sided side of the ordered porous carbon material. Topomorphology, optimize the conductivity and pore structure of the electrode.
It improves the rate performance of the battery and the conductivity of the electrodes, reduces the contact resistance, extends the cycle life of the battery, and avoids the reduction of the electrolyte utilization rate, which significantly increases the charging and discharge rate of the battery.
Smart Images

Figure CN115692724B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a carbon-coated foil material and a preparation method and application thereof. Background Art
[0002] Market development has put forward higher requirements for the energy density and rate performance of power lithium-ion batteries. Based on the existing process, the electrode is made thicker and rolled, and the volume ratio of the active material is increased by reducing the electrode porosity. Although the energy density of the battery can be increased, it will cause the battery to lose discharge capacity at a high rate.
[0003] During the charging and discharging process of lithium-ion batteries, Li + Diffusion between the positive and negative electrodes goes through three processes: 1) solid phase diffusion inside the active material particles; 2) charge exchange at the electrode / electrolyte interface; 3) diffusion inside the porous electrode. Each step may become the limiting step of the battery charge and discharge rate. Studies have shown that LFP / graphite system batteries with thin electrode design have good rate performance, but the rate performance will be greatly affected when the electrode becomes thicker, which also shows that Li + The diffusion process in the pores of thick porous electrodes is an important limiting factor in the rate performance of lithium-ion batteries. Therefore, considering the impact of thickening the electrode on the rate performance, the electrode foil needs to be further improved to solve the limitation of the battery charge and discharge rate.
[0004] Conventional foil is smooth foil. If a layer of conductive material (such as graphite, CNT or graphene) is coated on the surface of aluminum foil or copper foil, and the coating thickness is between 1 and 2 μm, it is called carbon-coated foil. Compared with smooth foil, carbon-coated foil can reduce the ohmic impedance of the electrode and enhance the bonding strength between the positive and negative electrode slurries and the current collector. When the positive electrode sheet resistance of the same surface density and different current collectors is measured using a sheet resistance tester, the positive electrode sheet contact resistance of carbon-coated aluminum foil is 0.1 to 1.0 Ω·cm 2 , the contact resistance of the positive electrode sheet using smooth aluminum foil is 30~50Ω·cm 2 The contact resistance of the positive electrode sheet using carbon-coated aluminum foil is reduced by at least one order of magnitude, and the DCR is also reduced from 120mΩ to 30mΩ. In addition, compared with conventional foil, carbon-coated foil can also reduce the amount of conductive agent and binder used, thereby improving the cycle life of the battery because the coated carbon layer has good conductivity.
[0005] For example, CN 109888296A discloses a method for preparing a carbon-coated current collector for a positive electrode of a lithium-ion battery, comprising the following steps: placing the current collector in an organic solvent containing nano-carbon powder and nano-titanium powder, and performing ultrasonic vibration cleaning; placing the treated current collector in a vacuum deposition chamber, introducing a reaction carbon source gas under a certain pressure, and performing a pre-nucleation treatment on the surface of the current collector; increasing the pressure in the vacuum deposition chamber and adjusting the flow rate of the reaction carbon source gas to promote the growth of crystal nuclei on the surface of the current collector to form a film; successfully depositing a uniform and dense carbon film layer on the surface of the current collector foil, which has higher peeling strength than the current collector prepared by the traditional method, reduces the risk of coating peeling, and increases the battery life, but the improvement in the overall performance of the battery is limited, especially the rate performance, which cannot be improved by improving the carbon-coated current collector.
[0006] Based on the above research, there is a need to provide a carbon-coated foil material, which can not only improve the conductivity of the electrode and reduce the contact resistance, but also improve the battery rate performance and solve the problem of limited battery charge and discharge rate. Summary of the invention
[0007] The object of the present invention is to provide a carbon-coated foil and a preparation method and application thereof. The carbon-coated foil not only has the advantages of conventional carbon-coated foil, so that the electrode has good conductivity and low contact resistance, but also improves the porosity of the electrode through the special structure of its carbon coating layer, improves the restriction of lithium ion diffusion in the pores inside the porous electrode, and makes the battery have excellent rate performance.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a carbon-coated foil, the carbon-coated foil comprising a foil and a carbon-coated layer on at least one side of the foil, the carbon-coated layer comprising a porous carbon material;
[0010] The porosity of the carbon coating layer at a side away from the foil is greater than the porosity of the side close to the foil.
[0011] The carbon-coated foil of the present invention improves the problem of limited diffusion of lithium ions in the pores inside the porous electrode from the perspective of the coating porosity. Specifically, the carbon-coated layer is set to a special structure with different porosities, wherein the porosity at the top far away from the foil side is larger, which is conducive to the diffusion of the electrolyte from the top to the inside, so that the electrolyte can fully infiltrate, while the porosity at the bottom close to the foil side is smaller than the porosity at the top. On the premise of ensuring full contact between the electrode material and the electrolyte, it avoids the problem of excessive electrolyte infiltration into the bottom and reducing the utilization rate of the electrolyte, thereby optimizing the rate performance of the electrode.
[0012] In addition, the carbon coating layer described in the present invention includes porous carbon materials. Porous carbon materials refer to carbon materials with different pore structures. According to the structural characteristics of porous carbon materials, they can be subdivided into disordered porous carbon materials and ordered porous carbon materials. The pore shapes of disordered porous carbon materials are irregular, and the pore size distribution range is wide; ordered porous carbon materials have the advantages of regular pore arrangement, controllable pore shape and pore size, and a narrow pore size distribution range; and porous carbon materials not only have the properties of carbon materials such as high chemical stability, good conductivity and low price, but also have the advantages of adjustable pore size, pore channel and morphology, and can be used to construct the special pore structure of the present invention, so that the carbon-coated foil can not only improve the conductivity of the electrode and reduce the contact resistance, but also improve the rate performance of the battery.
[0013] Preferably, the morphology of the porous carbon material includes a two-dimensional hexagonal morphology.
[0014] The porous carbon material described in the present invention is an ordered porous carbon material, and its specific morphology is a two-dimensional hexagonal. Compared with disordered porous carbon materials, ordered porous carbon materials have the advantages of regular pore arrangement, controllable pore shape, pore size and narrow pore size distribution range. Compared with spherical porous carbon materials, the porous carbon material with a two-dimensional hexagonal structure of the present invention is a porous carbon material with low curvature and high order, wherein the low curvature can enable electrons to pass quickly between the current collector and the active substance, thereby further improving the rate performance of the battery.
[0015] Preferably, the carbon coating layer has a gradient porosity.
[0016] In order to achieve the effect of fully wetting the electrode without reducing the utilization rate of the electrolyte, the porosity of the carbon coating layer is set to a gradient porosity that decreases from far away from the outside of the foil to close to the inside of the foil.
[0017] Preferably, the porosity of the carbon coating layer is 40-60%, for example, 40%, 45%, 50%, 55% or 60%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0018] Preferably, the thickness of the carbon coating layer is 1-2 μm, for example, it can be 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the thickness of the foil is 4-16 μm, for example, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm or 16 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Preferably, the foil comprises aluminum foil and / or copper foil.
[0021] In a second aspect, the present invention provides a method for preparing the carbon-coated foil as described in the first aspect, the preparation method comprising the following steps:
[0022] The porous carbon material is arranged on at least one side of the surface of the foil, which is then immersed in an etching solution. After the immersion, the foil is sintered to obtain the carbon-coated foil.
[0023] The structure in which the porosity of the carbon-coated layer away from the foil is greater than the porosity on the side close to the foil is obtained by etching. The carbon-coated layer is immersed in an etching solution and then sintered. The etching solution infiltrated in the porous carbon material can etch the surface of the material at a high temperature, thereby increasing the pore channels at the top of the carbon-coated layer and improving the porosity on the side away from the foil, thereby forming a special structure with small porosity at the bottom and large porosity at the top. Sintering during the reaction process further improves the stability of the carbon-coated foil and allows the etched gas to fully escape to form new pores. Therefore, the preparation method of the present invention can make the porosity of the carbon-coated layer controllable and form a specific structure.
[0024] Preferably, the method of placing the porous carbon material on the foil comprises: coating or spraying a slurry obtained by mixing the porous carbon material with water on the surface of the foil.
[0025] Preferably, the concentration of the etching solution is 3.5-6.5 mol / L, for example, it can be 3.5 mol / L, 4 mol / L, 4.5 mol / L, 5 mol / L, 5.5 mol / L, 6.0 mol / L or 6.5 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] Preferably, the etching solution includes any one of KOH, NaOH or HF.
[0027] When the present invention uses KOH for etching, the following reaction occurs: 4KOH+-CH 2 →K 2 CO 3 +K 2 O+3H 2 , K 2 CO 3 +2-C-→2K+3CO, the carbon element involved in the reaction becomes CO gas and escapes, and new pore channels appear at the position of the carbon element, making the porosity of the carbon coating controllable and the pore channels adjustable.
[0028] The sintering temperature and the concentration of the etching solution of the present invention will affect the etching effect, thereby affecting the porosity of the carbon coating layer. Therefore, they should be set within a reasonable range. If the etching temperature is too high, the time is too long or the concentration of the etching solution is too high, the carbon coating layer will have too many pore channels and too large pore diameters, resulting in the carbon coating layer having too large a material specific surface area, too much adsorbed electrolyte, and too much electrolyte concentrated in the carbon coating layer of the foil, which is not conducive to the infiltration of the active material. The electrolyte will react with the coating material to cause the structure of the coating material to be destroyed, thereby resulting in reduced adhesion and conductivity between the active substance and the foil, which in turn deteriorates the rate performance of the battery. When the etching temperature is too low, the time is too short or the concentration of the etching solution is too low, the structure of the carbon coating layer cannot be effectively constructed, and the technical effect of sufficient infiltration of the electrolyte and avoiding excessive electrolyte infiltration into the bottom cannot be achieved.
[0029] Preferably, the sintering is carried out in a protective atmosphere at a temperature of 500-700°C, for example, 500°C, 550°C, 600°C, 650°C or 700°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, the sintering time is 1-3 h, for example, 1 h, 1.25 h, 1.5 h, 1.75 h, 2 h, 2.25 h, 2.5 h, 2.75 h or 3 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the protective atmosphere comprises any one of argon, helium, neon or krypton, or a combination of at least two of them. Typical but non-limiting combinations include a combination of argon and helium, or a combination of neon and krypton.
[0032] Preferably, the method for preparing the porous carbon material comprises the following steps:
[0033] The porous carbon material is obtained by mixing, heating and calcining a phenol source, an organic source, a template, a catalyst and a pore-enlarging agent;
[0034] The organic source includes an aldehyde source and / or an amine source.
[0035] The present invention synthesizes an ordered porous carbon material through an organic-organic self-assembly method, wherein a phenolic resin generated by a phenol source and an organic source is used as a carbon source precursor, and there is a hydrogen bond or Coulomb force interaction between the carbon source precursor and the template agent, and then under the action of a pore expander, the template agent is removed by high temperature and the precursor is carbonized to remove impurities, thereby obtaining an ordered porous carbon material with a specific two-dimensional hexagonal structure; that is, the present invention can obtain the specific two-dimensional hexagonal porous carbon material of the present invention through the combination of a phenol source, an organic source, a template agent, a catalyst and a pore expander.
[0036] Preferably, the mass ratio of the phenol source, organic source, template, catalyst and pore expanding agent is (4-7):(0.5-1.5):1:(0.5-3):(1-3), for example, it can be 6:1:1:1.5:2, 4:1.5:1:0.5:1 or 7:0.5:1:3:3, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] The pore size of the porous carbon material of the present invention will increase with the increase of the amount of pore expanding agent. After increasing to a certain extent, the pore size will no longer change with the continued addition of pore expanding agent. Therefore, the content of the pore expanding agent affects the pore size and porosity of the porous carbon material of the present invention. If too little is added, the pores of the porous carbon material are limited and the beneficial effects of the present invention cannot be achieved. If too much porous carbon material is added, the pore size of the porous carbon material will be increased to a certain extent. If the pore size increases too large, the specific surface area of the carbon-coated material will be too large, and too much electrolyte will be adsorbed, which is not conducive to improving the battery performance.
[0038] Preferably, the pore expanding agent includes m-trimethylbenzene and / or PVB (polyvinyl butyral).
[0039] Preferably, the template comprises any one of P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer), F127 (polymer of propylene oxide and ethylene oxide) or F108 (polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer) or a combination of at least two thereof. Typical but non-limiting combinations include a combination of P123 and F127, and a combination of F127 or F108.
[0040] Preferably, the catalyst comprises L-lysine.
[0041] Preferably, the organic source includes any one of hexamethylenetetramine, formaldehyde or melamine, or a combination of at least two of them. Typical but non-limiting combinations include a combination of hexamethylenetetramine and formaldehyde, or a combination of hexamethylenetetramine and melamine.
[0042] Preferably, the phenolic source comprises hydroquinone and / or resorcinol.
[0043] Preferably, the heating temperature is 65-85°C, for example, 65°C, 70°C, 75°C, 80°C or 85°C, and the heating time is 24-35h, for example, 24h, 26h, 28h, 30h, 32h, 34h or 35h, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0044] Preferably, the heating is performed in a high pressure reactor.
[0045] Preferably, the calcination temperature is above 800°C, for example, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C or 1100°C, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0046] As a preferred technical solution of the method for preparing the carbon-coated foil of the present invention, the method comprises the following steps:
[0047] (1) mixing a phenol source, an organic source, a template, a catalyst and a pore-enlarging agent in a mass ratio of (4-7):(0.5-1.5):1:(0.5-3):(1-3), heating at 65-85° C. for 24-35 h and calcining at above 800° C. to obtain the porous carbon material;
[0048] The pore-enlarging agent includes m-trimethylbenzene and / or PVB, the template agent includes any one of P123, F127 or F108 or a combination of at least two thereof, and the catalyst includes L-lysine;
[0049] (2) placing the porous carbon material of step (1) on at least one side of the foil, and then immersing the foil in an etching solution. After the immersion, the foil is sintered in a protective atmosphere at a temperature of 500-700° C. for 1-3 hours to obtain the carbon-coated foil;
[0050] The concentration of the etching solution is 3.5-6.5 mol / L.
[0051] In a third aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the carbon-coated foil as described in the first aspect.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] (1) The present invention sets the carbon coating layer to a special structure, where the porosity at the top of the side away from the foil is larger, while the porosity at the bottom of the side close to the foil is smaller than that at the top. Under the premise of ensuring full contact between the electrode material and the electrolyte, the problem of excessive electrolyte infiltration into the bottom and reduced electrolyte utilization can be avoided, thereby optimizing the rate performance of the battery;
[0054] (2) The porous carbon material used in the carbon coating layer of the present invention is an ordered porous carbon material with a two-dimensional hexagonal morphology, which not only has the properties of carbon materials such as high chemical stability, good conductivity and low price, but also has the advantages of regular pore arrangement, controllable pore shape and pore size, and a narrow pore size distribution range. Compared with spherical porous carbon materials, the two-dimensional hexagonal porous carbon material has a low curvature and high order, which can allow electrons to pass quickly between the foil and the active material, thereby further improving the rate performance of the battery;
[0055] (3) The present invention etches the carbon-coated foil to obtain a structure in which the porosity of the carbon-coated layer on the side away from the foil is greater than the porosity on the side close to the foil, and then uses an organic-organic self-assembly method to synthesize a specific ordered porous carbon material, wherein a phenolic resin generated by a phenol source and an organic source is used as a carbon source precursor, and there is a hydrogen bond or Coulomb force interaction between the carbon source precursor and the template agent. Then, under the action of a pore expanding agent, the template agent is removed at high temperature and the precursor is carbonized, thereby obtaining an ordered porous carbon material with a specific two-dimensional hexagonal structure, so that the porous carbon material can be matched with the carbon-coated layer structure to achieve the effect of improving the battery rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 It is a schematic diagram of the structure of the porous carbon material described in Example 1 of the present invention. DETAILED DESCRIPTION
[0057] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0058] Example 1
[0059] This embodiment provides a carbon-coated foil material, the carbon-coated foil material comprises a foil sheet and a carbon-coated layer on both sides of the foil sheet, the carbon-coated layer comprises a porous carbon material with a two-dimensional hexagonal morphology, and the structural schematic diagram of the porous carbon material is shown in Figure 1 As shown;
[0060] The porosity of the carbon coating layer is 50%; the porosity of the carbon coating layer on the side away from the foil is greater than the porosity on the side close to the foil, and the porosity gradually decreases from the side away from the foil to the inner side close to the foil;
[0061] The foil is an aluminum foil with a thickness of 8 μm, and the thickness of the carbon coating layer is 1.5 μm;
[0062] The preparation method of the carbon-coated foil comprises the following steps:
[0063] (1) mixing hydroquinone, hexamethylenetetramine, P123, L-lysine and m-trimethylbenzene in a mass ratio of 6:1:1:1.5:2, heating in an autoclave at 75° C. for 30 h and calcining at 1000° C. to obtain the porous carbon material;
[0064] (2) placing the porous carbon material described in step (1) on both sides of the foil, and then immersing it in a KOH solution. After the immersion, the foil is sintered in an argon atmosphere at a temperature of 600° C. for 2 h to obtain the carbon-coated foil;
[0065] The concentration of the KOH solution is 4 mol / L.
[0066] Example 2
[0067] This embodiment provides a carbon-coated foil, the carbon-coated foil comprising a foil and a carbon-coated layer on both sides of the foil, the carbon-coated layer comprising a porous carbon material with a two-dimensional hexagonal morphology;
[0068] The porosity of the carbon coating layer is 60%; the porosity of the carbon coating layer on the side away from the foil is greater than the porosity on the side close to the foil, and the porosity gradually decreases from the side away from the foil to the inner side close to the foil;
[0069] The foil is an aluminum foil with a thickness of 6 μm, and the thickness of the carbon coating layer is 1 μm;
[0070] The preparation method of the carbon-coated foil comprises the following steps:
[0071] (1) resorcinol, formaldehyde, F127, L-lysine and PVB were mixed in a mass ratio of 4:0.5:1:0.5:1, heated in an autoclave at 65° C. for 35 h and calcined at 800° C. to obtain the porous carbon material;
[0072] (2) placing the porous carbon material described in step (1) on both sides of the foil, and then immersing it in an HF solution. After the immersion, the foil is sintered in a helium atmosphere at a temperature of 700° C. for 1 hour to obtain the carbon-coated foil;
[0073] The concentration of the HF solution is 6 mol / L.
[0074] Example 3
[0075] This embodiment provides a carbon-coated foil, the carbon-coated foil comprising a foil and a carbon-coated layer on both sides of the foil, the carbon-coated layer comprising a porous carbon material with a two-dimensional hexagonal morphology;
[0076] The porosity of the carbon coating layer is 40%; the porosity of the carbon coating layer on the side away from the foil is greater than the porosity on the side close to the foil, and the porosity gradually decreases from the side away from the foil to the inner side close to the foil;
[0077] The foil is a copper foil with a thickness of 16 μm, and the thickness of the carbon coating layer is 2 μm;
[0078] The preparation method of the carbon-coated foil comprises the following steps:
[0079] (1) mixing hydroquinone, melamine, F108, L-lysine and m-trimethylbenzene in a mass ratio of 7:1.5:1:3:3, heating in an autoclave at 85° C. for 24 h and calcining at 1000° C. to obtain the porous carbon material;
[0080] (2) placing the porous carbon material described in step (1) on both sides of the foil, and then immersing it in a KOH solution. After the immersion, the foil is sintered in an argon atmosphere at a temperature of 500° C. for 3 h to obtain the carbon-coated foil;
[0081] The concentration of the KOH solution is 3.5 mol / L.
[0082] Example 4
[0083] This embodiment provides a carbon-coated foil. The carbon-coated foil is the same as that in Embodiment 1 except that the sintering temperature in step (2) in the preparation method is 450° C., which changes the carbon-coated foil accordingly.
[0084] Example 5
[0085] This embodiment provides a carbon-coated foil. The carbon-coated foil is the same as that in Embodiment 1 except that the sintering temperature in step (2) in the preparation method is 550° C., which changes the carbon-coated foil accordingly.
[0086] Example 6
[0087] This embodiment provides a carbon-coated foil. The carbon-coated foil is the same as that in embodiment 1 except that in the preparation method, the concentration of the KOH solution in step (2) is 3 mol / L, which changes the carbon-coated foil accordingly.
[0088] Example 7
[0089] This embodiment provides a carbon-coated foil. The carbon-coated foil is the same as that in embodiment 1 except that in the preparation method, the concentration of the KOH solution in step (2) is 7 mol / L, which changes the carbon-coated foil accordingly.
[0090] Example 8
[0091] The present embodiment provides a carbon-coated foil. The carbon-coated foil is the same as that in Embodiment 1 except that in the preparation method, the mass ratio of hydroquinone, hexamethylenetetramine, P123, L-lysine and meta-trimethylbenzene in step (1) is 6:1:1:1.5:0.5, which changes the carbon-coated foil accordingly.
[0092] Example 9
[0093] The present embodiment provides a carbon-coated foil. The carbon-coated foil is the same as that in Embodiment 1 except that in the preparation method, the mass ratio of hydroquinone, hexamethylenetetramine, P123, L-lysine and meta-trimethylbenzene in step (1) is 6:1:1:1.5:3.5, which changes the carbon-coated foil accordingly.
[0094] Example 10
[0095] This embodiment provides a carbon-coated foil. The carbon-coated foil is the same as that of Embodiment 1 except that in the preparation method, in step (1), no m-trimethylbenzene is added to cause a corresponding change in the carbon-coated foil.
[0096] Embodiment 11
[0097] This embodiment provides a carbon-coated foil, which is the same as that of Embodiment 1 except that the porous carbon material in the carbon-coated layer is spherical in shape;
[0098] The preparation method of the spherical porous carbon material is as follows:
[0099] Hydroquinone and hexamethylenetetramine are mixed in a mass ratio of 6:1, heated in a high-pressure reactor at 75°C for 30 hours, and then calcined at 1000°C. During the calcination process, pore-forming agents nitrogen and water vapor are introduced to obtain the spherical porous carbon material.
[0100] Comparative Example 1
[0101] This comparative example provides a carbon-coated foil, in which the carbon-coated foil is the same as that in Example 1 except that the porosity of the carbon-coated layer on the side away from the foil is the same as the porosity on the side close to the foil.
[0102] In the preparation method of the carbon-coated foil, except that the foil is not immersed in KOH solution in step (2), but is directly sintered after being arranged, the rest is the same as that of Example 1.
[0103] Comparative Example 2
[0104] This comparative example provides a foil material, which is the same as Example 1 except that the foil material is not provided with a carbon coating layer.
[0105] The positive electrode active layer or the negative electrode active layer slurry is coated on the foil of the above embodiment and comparative example to prepare the positive electrode sheet and the negative electrode sheet, and then assembled into a lithium ion battery with a PE separator and a lithium hexafluorophosphate electrolyte, wherein the active material of the positive electrode sheet is LFP / NCM / LCO, and the active material of the negative electrode sheet is a graphite material / silicon-based material; the assembled lithium ion battery is tested for rate performance and DCR, and the rate performance test conditions are: testing its discharge capacity retention rate under 1C / 1C, 1C / 3C and 1C / 5C conditions, and the DCR test conditions are: 0.33C constant current charging to the specified SOC, leaving for 1h, 1C charging and discharging for 10s (recording interval 1s), and leaving for 10min; DCR calculation formula: |charge and discharge end voltage-charge and discharge start voltage| / 1C*1000.
[0106] The test results are shown in Table 1:
[0107] Table 1
[0108]
[0109] From Table 1 we can see that:
[0110] The carbon-coated foil provided by the present invention can not only reduce the internal resistance of the battery, but also improve the rate performance of the battery, and improve the restriction on the diffusion of lithium ions in the pores inside the porous electrode; it can be seen from Example 1 and Examples 4-11 that the sintering temperature and the concentration of the etching solution in step (2) will affect the etching effect, thereby affecting the porosity of the carbon-coated layer; the amount of the pore expander should be within a reasonable range so that the various raw materials in the porous carbon material can be matched to achieve the purpose of regulating the pore size and porosity; when the morphology of the porous carbon material changes, it will also affect the performance of the battery. The two-dimensional hexagonal morphology of the present invention allows electrons to pass quickly between the current collector and the active substance, thereby further improving the rate performance of the battery; at the same time, it can be seen from Example 1 and Comparative Examples 1-2 that, compared with empty foil and conventional carbon-coated current collectors, the present invention can significantly improve the battery rate performance and reduce the internal resistance.
[0111] In summary, the present invention provides a carbon-coated foil and a preparation method and application thereof. The carbon-coated foil not only has the advantages of conventional carbon-coated foil, so that the electrode has good conductivity and low contact resistance, but also improves the porosity of the electrode through the special structure of its carbon coating layer, thereby improving the restriction of lithium ion diffusion in the pores inside the porous electrode, so that the battery has excellent rate performance.
[0112] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A carbon-coated foil, characterized in that: The carbon-coated foil material comprises a foil and a carbon-coated layer on at least one side of the foil, wherein the carbon-coated layer comprises a porous carbon material; The porosity of the carbon coating layer on the side away from the foil is greater than the porosity on the side close to the foil; The preparation method of the carbon-coated foil comprises the following steps: The porous carbon material is arranged on at least one side of the surface of the foil, and then immersed in an etching solution, and the foil is sintered after the immersion is completed to obtain the carbon-coated foil; The method for preparing the porous carbon material comprises the following steps: The porous carbon material is obtained by mixing, heating and calcining a phenol source, an organic source, a template agent, a catalyst and a pore-enlarging agent.
2. The carbon-coated foil according to claim 1, characterized in that: The morphology of the porous carbon material includes a two-dimensional hexagonal morphology.
3. The carbon-coated foil according to claim 1, characterized in that: The carbon coating layer has a gradient porosity.
4. The carbon-coated foil according to claim 1, characterized in that: The porosity of the carbon coating layer is 40-60%.
5. The carbon-coated foil according to claim 1, characterized in that: The thickness of the carbon coating layer is 1-2 μm.
6. A method for preparing a carbon-coated foil as claimed in any one of claims 1 to 5, characterized in that: The preparation method of the carbon-coated foil comprises the following steps: The porous carbon material is arranged on at least one side of the surface of the foil, and then immersed in an etching solution, and the foil is sintered after the immersion is completed to obtain the carbon-coated foil; The method for preparing the porous carbon material comprises the following steps: The porous carbon material is obtained by mixing, heating and calcining a phenol source, an organic source, a template agent, a catalyst and a pore-enlarging agent.
7. The method for preparing the carbon-coated foil according to claim 6, characterized in that: The concentration of the etching solution is 3.5-6.5 mol / L.
8. The method for preparing the carbon-coated foil according to claim 6, characterized in that: The etching solution includes any one of KOH, NaOH or HF.
9. The method for preparing the carbon-coated foil according to claim 6, characterized in that: The sintering is carried out in a protective atmosphere at a temperature of 500-700°C.
10. The method for preparing the carbon-coated foil according to claim 6, characterized in that: The sintering time is 1-3h.
11. The preparation method according to claim 6, characterized in that: The organic source includes an aldehyde source and / or an amine source.
12. The method for preparing a porous carbon material according to claim 6, characterized in that: The mass ratio of the phenol source, the organic source, the template, the catalyst and the pore-enlarging agent is (4-7):(0.5-1.5):1:(0.5-3):(1-3).
13. The method for preparing a porous carbon material according to claim 6, characterized in that: The pore expanding agent includes m-trimethylbenzene and / or PVB.
14. The method for preparing a porous carbon material according to claim 6, characterized in that: The template includes any one of P123, F127 or F108 or a combination of at least two of them.
15. The method for preparing a porous carbon material according to claim 6, characterized in that: The catalyst includes L-lysine.
16. The method for preparing a porous carbon material according to claim 6, characterized in that: The organic source includes any one of hexamethylenetetramine, formaldehyde or melamine, or a combination of at least two of them.
17. The method for preparing a porous carbon material according to claim 6, characterized in that: The phenolic source includes hydroquinone and / or resorcinol.
18. The method for preparing a porous carbon material according to claim 6, characterized in that: The heating temperature is 65-85°C and the heating time is 24-35h.
19. The method for preparing a porous carbon material according to claim 6, characterized in that: The calcination temperature is above 800°C.
20. The preparation method according to claim 6, characterized in that: The preparation method comprises the following steps: (1) mixing a phenol source, an organic source, a template, a catalyst and a pore-enlarging agent in a mass ratio of (4-7):(0.5-1.5):1:(0.5-3):(1-3), heating at 65-85° C. for 24-35 h and calcining at above 800° C. to obtain the porous carbon material; The pore-enlarging agent includes m-trimethylbenzene and / or PVB, the template agent includes any one of P123, F127 or F108 or a combination of at least two thereof, and the catalyst includes L-lysine; (2) placing the porous carbon material of step (1) on at least one side of the foil, and then immersing the foil in an etching solution. After the immersion, the foil is sintered in a protective atmosphere at a temperature of 500-700° C. for 1-3 hours to obtain the carbon-coated foil; The concentration of the etching solution is 3.5-6.5 mol / L.
21. A lithium ion battery, characterized in that: The lithium-ion battery comprises the carbon-coated foil according to any one of claims 1 to 5.
Citation Information
Patent Citations
Preparation method for carbon-coated current collector of positive electrode of lithium ion battery
CN109888296A
Method for preparing lithium-ion secondary battery pole piece
CN102694150A
Organic porous framework negative electrode, preparation method thereof and battery
CN113594414A
High capacity battery electrode structures
US20120070741A1
